Profile of Determinant Factors on Drug Allergy Severity in Indonesian Children at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia - Bagas Triambodo; Azwin Mengindra Putera; Bambang Hermanto (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Drug allergy in children is a rare case that needs special attention. Identifying the factorsthat affect the severity of drug allergy is important for the improvement of drug allergy management inIndonesian children. Objective: to analyze the factors that influence drug allergy severity in Indonesianchildren. Methods: This study used a retrospective design and consecutive sampling in 2014-2018. The datacollected included sex, types of allergy-causing drugs, previous allergy history, parental allergy history, andclinical manifestations. The data were analyzed by using a logistic regression test where the statistical testresults were significant if p <0.05. Results: The average age of the participants was 93.00 ± 50.54 monthswith a median value of 84 (12 - 204) months. Drug allergy severity in children is influenced by severalthings, such as the type of drug (? = 5.76; 95% CI 1.29 - 25.70; p = 0.022), sex (? = 1.27; 95% CI 0.30 - 5.36;p = 0.743), previous allergy history (? = 2.44; 95% CI 0.10 - 58.67; p = 0.583), and a drug allergy history onparents (? = 0.65; 95% CI 0.06 - 6.75; p = 0.719). Conclusion: There is a significant relationship betweendrug allergy severity and the type of drug whereas sex, previous allergy history, and a history of allergy onparents do not find a significant connection.